Invasive Bacterial Infections in Infants Younger Than 60 Days With Skin and Soft Tissue Infections. Issue 6 (June 2021) - Foradori, Dana M.; Lopez, Michelle A.; Hall, Matt; Cruz, Andrea T.; Markham, Jessica L.; Colvin, Jeffrey D.; Nead, Jennifer A.; Queen, Mary Ann; Raphael, Jean L.; Wallace, Sowdhamini S.
Abstract : Objective: The objective of this study was to describe the frequency of invasive bacterial infections (IBIs) in young infants with skin and soft tissue infections (SSTIs) and the impact of IBI evaluation on disposition, length of stay (LOS), and cost. Methods: This retrospective (2009–2014) cohort study used data from 35 children's hospitals in the Pediatric Health Information System. We included infants younger than 60 days who presented to an emergency department (ED) with SSTI. Invasive bacterial infection was defined as bacteremia/sepsis, bone/joint infection, or bacterial meningitis. Readmission and return ED visits within 30 days were evaluated to identify missed IBIs for infants. Results: A total of 2734 infants were included (median age, 33 days; interquartile range [IQR], 21–44); 62% were hospitalized. Invasive bacterial infection was identified in 2%: bacteremia (1.8%), osteomyelitis (0.1%), and bacterial meningitis (0.1%). Hospitalization occurred in 78% of infants with blood cultures, 95% with cerebrospinal fluid cultures, and 23% without cultures. Median hospitalization LOS was 2 days (IQR, 1–3). Median cost was US $4943 for infants with cerebrospinal fluid cultures (IQR, US $3475–6780) compared with US $419 (IQR, US $215–1149) for infants without IBI evaluations ( P < 0.001). Five infants (0.2%) returned to the ED within 30 days with new IBI diagnoses (4 bacteremia, 1 meningitis). Conclusions: Invasive bacterial infection occurs infrequently in infants younger than 60 days who present to children's hospital EDs with SSTI. Bacteremia is the most common IBI. More extensive evaluation for IBI is associated with increased rate of admission, LOS, and cost. Further studies are needed to evaluate the safety of a limited IBI evaluation in young infants with SSTI. Abstract : Supplemental digital content is available in the text.